Cona Tezno 2028: urbanistično-arhitekturna delavnica (University of Maribor Press, 2017)
Tezno Zone 2028: Planning-architectural Workshop. Today, most once active industrial zones in Maribor are areas with high and diverse shares of brownfield or unused areas. Their “inactive” state has a high impact on the economic and urban development of the town. In view of the tradition, the identity of the town, and existing knowledge, the regeneration of industrial zones, which were active even a quarter of a century ago, is actually the crucial and only sensible possibility to establish sustainable strategy for the transformation of the town. The strategically planned regeneration of former and existing industrial zones may produce new urban high-quality areas in the town, which will be diverse in terms of their programmes, and will stimulate further urban development. Within the Sustainable City module of the master’s degree study programme of architecture, students prepared the conceptual design for the regeneration of the urban brownfield area before the entry to the Tezno Zone. The area between Ptujska cesta Street and the Tezno Zone is valued as a development zone and at the same time, as a “brownfield urban area.” In this area, the town and the Tezno Zone could develop a central area with regional functions, and establish central functions and areas for residents of the town and the local community.